The Power of Humor: Its Buffering Effect on Negative Job-related Affective Well-being against Job Demands - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS, DEPT PSYCHOLOGY, 2019)
The aim of this study is to investigate the moderating role of occupational humorous coping on the relationship between job demands and negative job-related affective well-being perception. Because of the increasing competition and difficult conditions, individuals encounter an increasingly complex working environment. In this context, every element that may cause a reduction in the employees' negative feelings should be taken into consideration. The model of the study is established in light of the foresight that occupational humor can reduce the negative job-related affective well-being perception which is expected to increase depending on the job demands. Employees working in the education and health sectors in Turkey (N = 319) participated in the study. Hierarchical regression and simple slope analysis revealed that as the occupational humorous coping tendency increases, the positive relationship between job demands and negative job-related affective well-being perception decreases. Employees whose job demands are high and whose tendencies for occupational humorous coping are low, have higher negative job-related affective well-being perception levels than the employees whose job demands and whose tendencies for occupational humorous coping are high. The findings of the study showed that in terms of negative job-related affective well-being perception in the face of high job demands, the employees with a weak tendency for occupational humorous coping are at a disadvantage in comparison to the employees with a stronger tendency for occupational humorous coping. These findings put forward that occupational humorous coping is an important skill not only in terms of contributing positively to the health of the employee, but also in terms of meeting job demands.
Keywords: Humor in workplace; job demands; job-related affective well-being; COUNTERPRODUCTIVE WORK BEHAVIOR; PSYCHOSOCIAL SAFETY CLIMATE; RESOURCES MODEL; BURNOUT; STRESSORS; MODERATOR; SENSE